Job Creation Law and Consequences in Determining Halâl Products: Analysis of the Halâl Product Fatwa Committee - Iswanto, Bambang (al-'adalah, 2023)
The Halâl Product Fatwa Committee is a new institution constructed in the Job Creation Law. Its authority is to determine whether consumer goods are halâl or harâm. This role has received two views: on the one hand, it is an attempt to negate the authority of the Ulema Council Indonesia (MUI), on the other hand, it shows that the government is interfering in religious affairs. This article attempts to present a review of the conception of government power, followed by regulations regarding the determination of halâl status in the Job Creation Law including its implications on institutional arrangements for administering halâl products. This research uses a combination of normative legal approaches with conceptual and statutory approaches. The research results show that: First, government power is an institution that is obliged to carry out governance issues. Second, the Halâl Product Fatwa Committee and its authority have the potential to eliminate the role of the MUI. Third, structuring can be done by unifying institutions administering Halâl guarantees or forming non-structural government institutions. This aims to create legal order and at the same time ensure that the MUI's institutional role is not lost.